Los problemas más preocupantes del Perú - Clinton, Richard L. (1998)
The problem singled out by this sample of 170 highly educated and well positioned opinion leaders of diverse professions (125 men and 45 women) are indeed serious: 1) poverty (56%), 2) un- and underemployment (53%), 3) lack of institutionalization (45%), 4) the educational system (29%), 5) street violence (20%) and, 6) centralism (13%). Surprisingly, however, a number of equally serious problems were mentioned by less than 2% of the opinion leaders: injustice, corruption, rapid population growth, foreign intervention, and narcotrafficking. The prospects for Peru 's development are seen by 57% of the sample as either very promising (9%) or promising (48%); only 11% perceive these prospects as doubtful (10%) or very doubtful (1%). The optimism prevalent among these elites may inhibit recognition of and therefore effective responses to Peru 's most serious problems.